Investigations of indole-alkaloid biogenesis through synthesis - Stuart, Jake (The University of Edinburgh, 2023)
Biomimetic synthesis is a blanket term used to describe a great number of synthetic endeavours, broadly encapsulated by using reactions and materials available during organic metabolism. Herein, we will be utilising biomimicry to interrogate hypotheses for the biogenesis a complex bis-indole natural product; (+)-dievodiamine. As well as this, we will share our attempts to synthesise natural products in a concise way, with high atom economy. Chapter 1 is an introduction to metabolism and the biogenesis of natural products derived from the shikimic acid pathway. Biomimetic syntheses of related natural products will be discussed, as well as a literature review summarising the synthesis of pentacyclic, quinazolinocarboline natural products related to (+)-dievodiamine. The isolation and only known synthesis (+)-dievodiamine will be discussed, as well as our proposed biosynthetic pathway and synthetic plan towards (+)-dievodiamine. Chapter 2 describes the discovery of a unique deprotonation/retro-6π electrocyclisation cascade which supports our proposed biogenesis of (+)-dievodiamine. As well as this, attempts to synthesise (+)-dievodiamine via a vinylogous Mannich reaction are presented, which provides insights into the redox chemistry of evodiamine (the formal monomer of (+)-dievodiamine). Chapter 3 focuses on a route towards (+)-dievodiamine based on nonribosomal peptide synthetase mediated alkaloids. The synthesis of a tri-amide oligomer composed of tryptophan, tryptamine and two units of N-methyl anthranilic acid will be discussed. Beyond that, attempted functionalisation and cyclisation chemistry on a model peptide intermediate will be discussed. Finally, attempts to install a C1-unit within the mature peptide oligomer will be described. Chapter 4 follows-on in our attempts in the synthesis of (+)-dievodiamine by late-stage cyclisation, described in the chapter prior. This strategy we labelled the convergent route, it focuses on a synthesis of (+)-dievodiamine from a pre-functionalised the oligomer from Chapter 3. We will also show that some of the chemistry attempted prior can be achieved simply by removal of a methyl group from the intermediate. We will attempt to complete the synthesis of the natural product through a Pictet−Spengler cyclisation and late-stage ring closure.
Keywords: indole-alkaloid biogenesis; Biomimetic synthesis; shikimic acid pathway; (+)-dievodiamine; vinylogous Mannich reaction; model peptide inter; mature peptide oligomer; Pictet−Spengler cyclisation